FAO/WHO GIFT (Global Individual Food consumption data Tool): a global repository for harmonised individual quantitative food consumption studies. Issue 4 (28th February 2019) - Leclercq, C.; Allemand, P.; Balcerzak, A.; Branca, F.; Sousa, R. F.; Lartey, A.; Lipp, M.; Quadros, V. P.; Verger, P.
Abstract : Knowing who eats what, understanding the various eating habits of different population groups, according to the geographical area, is critical to develop evidence-based policies for nutrition and food safety. The FAO/WHO Global Individual Food consumption data Tool (FAO/WHO GIFT) is a novel open-access online platform, hosted by FAO and supported by WHO, providing access to harmonised individual quantitative food consumption (IQFC) data, especially in low- and middle-income countries (LMIC). FAO/WHO GIFT is a growing repository, which will serve as the global FAO/WHO hub to disseminate IQFC microdata. Currently five datasets from LMIC are available for dissemination, and an additional fifty datasets will be made available by 2022. To facilitate the use of these data by policy makers, ready-to-use food-based indicators are provided for an overview of key data according to population segments and food groups. FAO/WHO GIFT also provides an inventory of existing IQFC data worldwide, which currently contains detailed information on 188 surveys conducted in seventy-two countries. In order for end-users to be able to aggregate the available data, all datasets are harmonised with the European Food Safety Authority's food classification and description system FoodEx2 (modified for global use). This harmonisation is aimed at enhancing the consistency and reliability of nutrient intake and dietary exposure assessments. FAO/WHO GIFT is developed in synergy with other global initiatives aimed at increasing the quality, availability and use of IQFC data in LMIC to enable evidence-based decision-making and policy development for better nutrition and food safety.